Proyeksi Hasil Belajar Melalui Bernalar Kritis, Kreatif dan Mandiri Untuk Mewujudkan Profil Pelajar Pancasila - Nurhadifah Amaliyah; Waddi Fatimah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The application of the value of learning activities is one of the efforts to strengthen student character. Linear efforts with the Ministry of Education and Culture's commitment to realize Pancasila Students. The concept of realizing students with good character, high competence, able to compete globally and reflect the noble values of Pancasila. Tested to project learning outcomes in the learning process through critical, creative and independent reasoning, realizing the profile of Pancasila students. The type of research is quantitative correlation. Respondents were 34 students from 136 population. Instruments in the form of questionnaires were analyzed descriptively and inferentially. The results showed that the variables of critical reasoning (X1), creative (X2) and independent (X3) simultaneously had a relationship to student learning outcomes (Y). The indicator sig ? value generated is 0.000 and smaller than 0.05. Realizing the profile of Pancasila students can integrate Pancasila values in every action and decision of students. Critical and creative thinking skills are used to face various moral and ethical challenges. Independently living daily life, still upholding the values of Pancasila. Through projection, having academic intelligence, forming character in accordance with the Pancasila philosophy of life, creating dignified, fair, and highly competitive individuals facing global dynamics.